Taxonomy of European Damaeidae (Acari: Oribatida) VII. Redescription of Neobelba pseudopapillipes Bulanova-Zachvatkina, 1967 with comments on its generic status - Miko, Ladislav; Kolesnikov, Vasiliy B. (Zootaxa, 2014)
We redescribe Neobelba pseudopapillipes Bulanova-Zachvatkina, 1967, single known species of Neobelba Bulanova-Zachvatkina, 1967, based on the material collected in Russia and Slovakia. The species shares many important characters of Metabelba Grandjean, 1936, particularly of the subgenus M. (Pateribelba) Mourek, Miko et Bernini, 2011. It can be easily distinguished by presence of companion seta d, coupled with solenidion on tibia IV. As the original material of Bulanova-Zachvatkina was lost, neotype and 14 paraneotypes from Voronezh region, Russia are newly designated. Based on the neotype redescription, Neobelba was re-defined and the new status was proposed. Synonymy with Metabelba s. str. as proposed by Subías (2013) is rejected, and Neobelba is considered to be a separate subgenus of Metabelba, as earlier proposed by Subías (2004). Present distribution of Metabelba (Neobelba) pseudopapillipes (Bulanova-Zachvatkina, 1967) and known ecological data on the species are provided.